THE ESSENCE OF IMPROVING QUALITATIVE COMPETENCE IN PRE-SCHOOL STUDENTS AND THE PRACTICAL STATUS OF THE PROBLEM - Kurbanova Mukhtasarkhan Bahromovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation. This article describes the pedagogical system, the system for the development of qualimetric competence, its main components, the composition of each module and their content and essence in describing the effective functioning and development of the system.